Design of aquaponics water monitoring system using Arduino microcontroller - Murad, S.A.Z.; Harun, A.; Shaiful Nizam, Mohyar; Rohana, Sapawi; Ten, S.Y. (American Institute of Physics Inc., 2017)
This paper describes the design of aquaponics water monitoring system using Arduino microcontroller. Arduino Development Environment (IDE) software is used to develop a program for the microcontroller to communicate with multiple sensors and other hardware. The circuit of pH sensor, temperature sensor, water sensor, servo, liquid crystal displays (LCD), peristaltic pump, solar and Global System for Mobile communication (GSM) are constructed and connected to the system. The system powered by a rechargeable battery using solar energy. When the results of pH, temperature and water sensor are out of range, a notification message will be sent to a mobile phone through GSM. If the pH of water is out of range, peristaltic pump is automatic on to maintain back the pH value of water. The water sensor is fixed in the siphon outlet water flow to detect water flow from grow bed to the fish tank. In addition, servo is used to auto feeding the fish for every 12 hours. Meanwhile, the LCD is indicated the pH, temperature, siphon outlet water flow and remaining time for the next feeding cycle. The pH and temperature of water are set in the ranges of 6 to 7 and 25 °C to 30 °C, respectively.